(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Carica papaya L., family Caricaceae, is well-known for its various nutritional values and pharmacological activities. Several parts of the Carica papaya, such as the leaves, fruits and seeds are being used for their potential health benefits in the traditional system. The prime objective of this review work is to explore traditional uses, phytoconstituents and pharmacological activities of Carica papaya. Using electronic sources such as PubMed, Google Scholar, and Science Direct, an entire literature search was conducted to compile information and data. In this review work, the findings show that Carica papaya contains various bioactive compounds such as flavonoids, alkaloids, tannins and saponins exhibiting the pharmacological activities including anti-inflammatory, antimicrobial, and antioxidant properties. Carica papaya shows potential in treating notable health conditions, including digestive, inflammation, and infections. But the importance of the identification of molecular targets and toxicological aspects should be considered for new drug discovery and development. Dhaka Univ. J. Pharm. Sci. 25(1): 81-91, 2026 (June)